Trends in the Use of Minimally Invasive Adnexal Surgery in the United States. Issue 5 (November 2021) - Dioun, Shayan; Huang, Yongmei; Melamed, Alexander; Gockley, Allison; St. Clair, Caryn M.; Hou, June Y.; Tergas, Ana I.; Khoury-Collado, Fady; Hershman, Dawn L.; Wright, Jason D.
Abstract : OBJECTIVE: To examine the utilization of minimally invasive adnexal surgery, including ovarian cystectomy and oophorectomy, among women with benign gynecologic diseases and compare the associated morbidity and mortality of minimally invasive and open surgery. METHODS: Women with benign ovarian pathology who underwent an ovarian cystectomy or oophorectomy from 2016 through 2018 in the Nationwide Ambulatory Surgery Sample and Nationwide Inpatient Sample databases were included. Patients with a diagnosis of gynecologic malignancy or concurrent hysterectomy were excluded. Population-level weighted estimates were developed, and perioperative morbidity, mortality, and hospital charges were examined based on surgical approach for each procedure. RESULTS: The cohort included 351, 207 women who underwent oophorectomy and 220, 893 women who underwent cystectomy, when weighted representing 547, 836 and 328, 408 patients, respectively, nationwide. A minimally invasive surgical approach was used in 294, 190 (89.6%) patients who underwent ovarian cystectomy, and in 478, 402 (87.3%) of patients who underwent oophorectomy. Use of minimally invasive surgery for cystectomy increased from 88.7% in 2016 to 91.0% in 2018, and the rate of minimally invasive surgery for oophorectomy increased from 85.8% to 88.7% over the same time period ( P <.001 for both). The complication rates for ovarian cystectomy were 2.7% for minimally invasive surgery and 8.8% for laparotomy ( P <.001); for oophorectomy the complication rate was 3.1% for minimally invasive surgery and 22.9% for laparotomy ( P <.001). CONCLUSION: Minimally invasive surgery is used in the majority of women who are undergoing oophorectomy and ovarian cystectomy for benign indications. Compared with laparotomy, minimally invasive surgery is associated with fewer complications. Abstract : Minimally invasive adnexal surgery is used in the majority of women undergoing oophorectomy and ovarian cystectomy for benign indications.